Building a common vision for sustainable food and agriculture : principles and approaches (Food and Agriculture Organization of the United Nations RomeIT, 2014)
Offers a common vision of the agriculture sector and of the inter-sectoral synergies aimed at making agriculture more productive and sustainable.
Keywords: AGRICULTURAL SECTOR